Eponyms in forensic pathology - Nečas, Pavel; Hejna, Petr (Forensic science, medicine, and pathology, 2012)
The phenomenon of eponymous terms in forensic pathology is described in this paper. The authors analyzed representative textbooks (monographs) dealing with forensic pathology in both English and German and identified several eponymous terms. The paper aims to present to the reader the most important eponymous terms in forensic pathology. Included in the paper are the following terms: Beckwith's Sign, Casper's Rule, Krönlein's Shot, Lichtenberg's Figures, Nysten's Law, Paltauf's Spots, Puppe's Rule, Sehrt's Sign, Simon's Sign, Sveshnikov's Sign, Tardieu's Spots, Wischnewski Spots, Wydler's Sign. The spread of eponymous terms throughout various languages is mentioned. The linguistic basis of such terms as well as their advantages and disadvantages in specialist fields, and indeed in even wider circles, is discussed. The authors state that the main function of these terms is to facilitate the open flow of unambiguous information among scholars. Eponymous terms in forensic pathology are characteristic for the German speaking countries and for all countries influenced by the German school of forensic pathology. Their usage in the Anglo-Saxon world is much less widespread, meaning they do not occur very often in English monographs and textbooks.
Keywords: eponyma; lidé; Forensic Pathology; Eponyms; soudní patologie; Humans